New species and records of the genus Hercostomus Loew (Diptera: Dolichopodidae) from Thailand mangroves, with notes on the Hercostomus fauna of Singapore mangroves - Samoh, Abdulloh; Grootaert, Patrick (Zootaxa, 2024)
The long-legged fly genus Hercostomus Loew, 1857 is reported for the first time from mangrove habitats in Thailand. Two new species, H. obtusus sp. nov. and H. squamatus sp. nov. are described based on external morphology and supported by NGS barcoding. Four described species, namely, H. brevicornis Zhang, Yang & Grootaert, 2008, H. brevidigitalis Zhang, Yang & Grootaert, 2008, H. lanceolatus Zhang, Yang & Grootaert, 2008, and H. plumatus Zhang, Yang & Grootaert, 2008, previously known only from Singapore mangroves, are recorded for the first time from Thailand mangroves. In addition, species distributions are mapped and taxonomic notes are provided.